2020
DOI: 10.1002/er.5692
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation on heat transfer characteristics of helium‐xenon gas mixture

Abstract: Summary Helium‐Xenon (He‐Xe) gas mixture featured with low Prandtl number is increasingly used in various energy devices as heat‐carrying agent. To figure out the heat transfer characteristics of He‐Xe gas mixture in uniformly heated circular and tri‐lobe channels, numerical investigations are conducted and presented in the article. The adopted calculation models are validated by comparison between simulation results and experimental data. The local and total heat transfer characteristics are obtained, and new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The manufacturing plans were investigated [3] and measurements were made to corroborate that the built reactor was true to the plans. The containment model was created with CAD and exported as a mesh file into Ansys CFX, from the studies conducted by [23].…”
Section: Gas Behavior and Hydrogen Explosion Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…The manufacturing plans were investigated [3] and measurements were made to corroborate that the built reactor was true to the plans. The containment model was created with CAD and exported as a mesh file into Ansys CFX, from the studies conducted by [23].…”
Section: Gas Behavior and Hydrogen Explosion Riskmentioning
confidence: 99%
“…The results showed that the flow pattern and velocity were affected by changes in the coolant temperature and system pressure. The turbulent flow and heat transfer of gas mixtures in circular tubes have also been investigated using CFD [3]. The authors conducted a numerical investigation of the turbulent flow and heat transfer of a helium-xenon gas mixture in a circular tube.…”
Section: Introductionmentioning
confidence: 99%
“…As a modern research method, numerical simulation can accurately calculate the velocitytemperature distribution in the flow pattern, obtaining the flow field's heat transfer capacity. Qin et al [29] explored the heat transfer characteristics of helium-xenon in the uniformly heated circular channel and tri-lobe channel based on the SST k-ω model through numerical simulation. Qin et al found a large temperature gradient in the channels' corner thanks to the simulation's ability to capture the flow domain's detail.…”
Section: Introductionmentioning
confidence: 99%